STRATEGI PENINGKATAN KINERJA PEGAWAI - Asri, Novia Mega; Armanu, Armanu (Jurnal Kewirausahaan dan Inovasi, 2023)
The success of an organization to achieve its objectives and targets is determined by the performance of its human resource. This also applies to governmental organizations. However, there are problems in their performance, so employee performance management is expected to be able to enhance employees’ quality and professionalism. The objective of this research is to describe the external and internal environments of the Center for the Development and Empowerment of Educators and Education Personnel in Civil and Social Sciences (PPPPTK PKn and IPS) in Batu and to identify strategies to improve its employees’ performance. The data of this descriptive qualitative case study was harvested from observations, interviews, and documentations and was processed using SWOT analysis. This study finds that the performance of the agency’s employees has not been optimal due to poor disciplinary enforcement, performance assessment system, and career development system. The strategies to improve them are using online-based information technology, creating good workplace environment that support organizational performance, enhancing the effectiveness of organization’s internal communication.